Monitoring the training load in the race: Physiological and methodological aspects in the practical applicability of this modality: Monitoramento da Carga de treinamento na Corrida (Research, Society and Development, 2021)
In the running, the demand for adjustments to optimize the stimuli for obtaining better performance is relevant and indispensable. With that, the prescription for running training, be it short, medium and long distance, must be strictly adequate, as well as the entire recovery process, thus allowing for better physiological adaptations. For this, the control of the training load is something essential and in addition, the possibility of obtaining positive responses becomes greater, since the individual will be more protected from possible stresses resulting from the accumulation of fatigue. The control of the training load is a great tool for coaches to identify the moment to continue in the application of stimuli, as well as in the control of these before the athletes. With this, it is possible to avoid excessive overloads that can expose the athlete to a decrease in performance and even an injury and, in the race, this intervention is extremely important. Among the types of assessments used, the use of calculating the subjective perception of the session effort (RPE), heart rate (HR), heart rate variability (HRV) and biochemical markers (lactate, creatine kinase and salivary cortisol) are the most common among the measurements of the training load (or internal load). The purpose of this review was to describe the efficiency of these methods and responses that make it possible to assess the training load in the running modality. Several studies have demonstrated, through different tools for this type of analysis, the efficiency and above all the importance of the procedure of analysis and evaluation of the training load. Indirect procedures, such as PSE and HRV, have been correlated by different studies, with other internal indicators of exercise intensity, such as, for example, oxygen consumption, heart rate and lactate concentration. However, it is necessary to carry out more studies investigating the training load in athletes / runners, in order to have more information about this extremely important tool for this modality.